Well-being of veterinarians in rural and urban areas - Gonschor, Cecile; Pohl, Robert; Woitha, Ulrike; Thielmann, Beatrice; Böckelmann, Irina (Frontiers in Veterinary Science, 2023)
Introduction: The field of veterinary medicine is characterized by a variety of challenging working conditions. The alarmingly low mental well-being of veterinarians has been examined from various perspectives. However, the influence of work location on the well-being of veterinary professionals has scarcely been investigated. The aim of the study was therefore to analyze the well-being of German veterinarians and to determine whether there is a correlation between well-being and work location. Methods: As part of a cross-sectional study, 999 veterinary professionals answered questions regarding their work location (self-designed questions) and well-being (WHO-Five Well-being Index, WHO-5). A differentiation was made according to work location: urban cities (population >100,000), medium/small cities (population <100,000 inhabitants), and rural areas. Results: Overall, the surveyed veterinarians had low well-being (ranging from 56.8% in rural areas to 61.3% in medium/small towns). The results of the general linear model indicated a significant difference in the WHO total score among veterinarians from different work locations (p < 0.001). However, when sex, age, type of employment, and field of specialization were included in the analysis, no significant between-subject effects were found. Conclusion: According to the results, work location does not seem to have a significant influence on the well-being of veterinarians and therefore may be of lower priority in the development and implementation of interventions. However, further investigation of work-related predictors of the mental health of veterinarians is recommended, as the results indicate a low well-being among these professionals.